2019
DOI: 10.1123/jpah.2018-0675
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Activity on the Physical and Psychosocial Health of Youth With Intellectual Disabilities: A Systematic Review and Meta-Analysis

Abstract: Background: The physical and psychosocial benefits of physical activity for typically developing youth are well established; however, its impact on youth with intellectual disabilities is not as well understood. The aims of this review and meta-analysis were to synthesize the literature and quantify the effects of physical activity on the physical and psychosocial health of youth with intellectual disabilities. Method: Studies meeting the inclusion criteria were grouped by their focus on physical health and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
78
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 46 publications
3
78
1
3
Order By: Relevance
“…As in the general population, being physically active was positively associated with cardiorespiratory endurance, muscular strength and endurance, and flexibility in adults with ID, suggesting that these factors can be improved by increasing PA and decreasing SA. These results are in agreement with an intervention study in adults with ID that indicated positive effects of PA on several physical fitness outcomes [ 49 ]. Moreover, previous research has indicated that people with ID engage less frequently in PA [ 3 ], are less physically fit [ 5 ], live more sedentary lives [ 4 ], and are more likely to be overweight or obese [ 6 ] than the general population.…”
Section: Discussionsupporting
confidence: 91%
“…As in the general population, being physically active was positively associated with cardiorespiratory endurance, muscular strength and endurance, and flexibility in adults with ID, suggesting that these factors can be improved by increasing PA and decreasing SA. These results are in agreement with an intervention study in adults with ID that indicated positive effects of PA on several physical fitness outcomes [ 49 ]. Moreover, previous research has indicated that people with ID engage less frequently in PA [ 3 ], are less physically fit [ 5 ], live more sedentary lives [ 4 ], and are more likely to be overweight or obese [ 6 ] than the general population.…”
Section: Discussionsupporting
confidence: 91%
“…Another systematic review demonstrated that self-efficacy could be an essential factor associated with PA in children with physical disabilities ( Bloemen et al, 2015 ). Other reviews have found positive effects of PA on several mental health dimensions for children with SEN, including psychological well-being ( Arbour-Nicitopoulos et al, 2018 ), self-efficacy ( Kapsal et al, 2019 ), self-esteem ( Dahan-Oliel et al, 2012 ), anxiety ( Cerrillo-Urbina et al, 2015 ), and depression ( Veneri et al, 2018 ). One review suggested that the effects of PA might be moderated by age, environment, and social factors ( Rodriguez-Ayllon et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A literatura reforça os benefícios da prática regular de AF para as PCD, tais como melhora de medidas fisiológicas (redução do estresse oxidativo e peso corporal), aptidão física (aumento da força muscular, resistência cardiorrespiratória e equilíbrio), cognição (melhora da função cognitiva global, velocidade de processamento e atenção) e fatores neuropsicológicos (aumento da autoestima e redução do estresse e depressão) 20,21,23,24 . Por isso, se faz necessário orientar sobre as recomendações de AF para os diferentes ciclos de vida.…”
Section: Discussionunclassified